2006
DOI: 10.1093/ptj/86.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Arm Volume Measurements for Assessment of Lymphedema

Abstract: Background and Purpose. Arm lymphedema following breast cancer surgery is a continuing problem. In this study, we assessed the reliability and validity of circumferential measurements and water displacement for measuring upper-limb volume. Subjects. Participants included subjects who had had breast cancer surgery, including axillary dissection—19 with and 22 without a diagnosis of arm lymphedema—and 25 control subjects. Methods. Two raters measured each subject by using circumferential tape measurements at spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
169
3
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(179 citation statements)
references
References 15 publications
2
169
3
5
Order By: Relevance
“…6 Data also indicated that 2-point measures with a 5% circumference change threshold have high sensitivity and specificity (80% and 71%, respectively), close correlation to limb volume calculations using water displacement, and compare favorably with the sensitivity and specificity of multiple-point measurements with high test-retest and interrater reliability. [42][43][44] In addition, circumference measurements provide reliable calculations for differences >0.4 cm. 45 Further, water displacement techniques have practical difficulties such as space issues, spillage, and the need for sterile technique for each measurement.…”
Section: Lymphedema Measurementmentioning
confidence: 99%
“…6 Data also indicated that 2-point measures with a 5% circumference change threshold have high sensitivity and specificity (80% and 71%, respectively), close correlation to limb volume calculations using water displacement, and compare favorably with the sensitivity and specificity of multiple-point measurements with high test-retest and interrater reliability. [42][43][44] In addition, circumference measurements provide reliable calculations for differences >0.4 cm. 45 Further, water displacement techniques have practical difficulties such as space issues, spillage, and the need for sterile technique for each measurement.…”
Section: Lymphedema Measurementmentioning
confidence: 99%
“…This is important if the data have to be used for volume prediction. Therefore, the markings are based on anatomic landmarks as suggested by Taylor et al (2006). The first mark was placed at half the distance between the acromium and epicondylus lateralis humeri (mid-humerus).…”
Section: Normative Datamentioning
confidence: 99%
“…TCV (excluding the hand, as it is not conical) was chosen for this study as volume changes correlate well with water volumetry but it is liable to overestimate the absolute volumes. 9 In future studies, the use of bioimpedance measures may be an option; similarly, optoelectronic perometry could be used to quantify changes in the fluid composition of the limb. The use of a validated questionnaire (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This formula has been shown to have good interrater and test-retest reliability as well as correlating well with water volumetry methods. 9,10 The procedure was performed in a day surgery setting with local anaesthetic infiltration at the donor site (groin) and the two recipient sites (wrist and supratrochlear). A small dose of intravenous ketamine and/or midazolam was given as sedation.…”
Section: Methodsmentioning
confidence: 99%